An Investment Selection In Transportation Subsector Using Mabac Method - Andre Hasudungan Lubis; Sucitra Dewi; Fauziah Rahman (Sean Institute, 2022)
The transportation sector is a sub-sector of the infrastructure sector, which plays an important role in economic development in Indonesia. In buying shares, investors must have the right considerations to choose the right and proper company. Thus, the emergence of a decision-making model to assist investors in purchasing shares is a necessity. The study used the MABAC method to select stock investments among 12 companies engaged in the transportation subsector on the Indonesia Stock Exchange (IDX). The criteria used are several financial ratios, namely PER, DER, ROE, and DPR. On the other hand, the CRITIC method is used as a determinant of the weight value of each criterion. The results of the study show that PT Garuda Indonesia (Persero) Tbk is the company that ranks first as the most appropriate company for buying shares.